Anti-Platelet Therapy and Aspirin Resistance - Clinically and Chemically Relevant? - Rafferty, M.; R. Walters, M.; Dawson, J. (Current Medicinal Chemistry, 2010)
Platelets play a central role in the pathogenesis of the atherothrombosis which ultimately causes myocardial infarction, stroke and peripheral vascular disease. Commonly used oral anti-platelet drugs include aspirin (an irreversible inhibitor of cyclo-oxygenase), clopidogrel (an ADP receptor antagonist), other thienopyridines such as ticlopidine and prasgruel, and dipyridamole (an inhibitor of adenosine reuptake and platelet phosphodiesterase). Newer agents are in development and one, ticagrelor, a reversible ADP receptor antagonist has shown promise. Despite their proven benefit, recurrent vascular events still occur in those taking anti-platelet drugs. This has led to the concept of anti-platelet resistance, most commonly aspirin resistance as this drug is the cornerstone of most regimens. The causes of aspirin resistance are numerous but potential mechanisms include lack of patient adherence, non COX-1 mediated thromboxane A2 synthesis, increased activity of alternate platelet activation pathways, interference of aspirin action by other drugs and probably pharmacogenetic factors. Measurement of platelet response to aspirin is made possible using a number of in-vitro laboratory assays of platelet function which include measurement of thromboxane A2 metabolites as well as newer point-of-care assays of platelet aggregation. The phenomenon of aspirin resistance is important as it raises the possibility of developing strategies to identify those who respond best to a particular anti-platelet regimen, or to development of newer anti-platelet therapies to which more patients respond. This review discusses important aspects of aspirin resistance both in terms of clinical medicine, alternative anti-platelet strategies, and the potential to overcome its various causes.
Keywords: Polymorphisms